Teamship Competence - Farasi, Sanida Nisa; Anshori, Mochammad Isa (Nomico, 2024)
Team competency is an important aspect in achieving overall team and organizational success. This research aims to explain the concept of team competency, highlighting the importance of individual skills and collaboration in achieving optimal performance in teams. Team competencies include the skills, knowledge, attitudes, and individual characteristics that contribute to the team's ability to achieve goals effectively. Strong individual skills, such as effective communication, problem-solving abilities, good leadership, and adaptability to change, are essential in building solid team competencies. In addition, good collaboration between team members, including the ability to work together, listen, give and receive feedback, is also an important factor in achieving high team performance.